A modified thermodynamic sea ice model and its application. (October 2022) - Fang, Yongjie; Wu, Tongwen; Hu, Aixue; Chu, Min
Abstract: A modified thermodynamic sea ice model suitable for large-scale climate simulations is described. Originated from the Winton's three-layer model framework, this new model includes several improvements in the vertical thermodynamics: (1) the number of ice layers increases from two to three; (2) the snow heat capacity is included; (3) a vertically varying salinity profile is implemented; and (4) a temperature- and salinity-dependent heat conductivity parameterization scheme is introduced. A non-iterative fully implicit time-stepping scheme similar to Winton's model is used to calculate the temperature of ice and snow. Results from a series of one-dimensional experiments show that equilibrium ice thickness in the modified model is increased by 45 cm when compared with the original Winton's model. All modifications mentioned above contribute to this change of ice thickness, among which the increase of ice layer has the most significant effect. Experiments using the Modular Ocean Model version 4 (MOM4) coupled with the modified model show an improved sea ice simulation which includes an increase in both the sea ice volume and thickness over the entire Arctic region, confirming the above founding. However, contrary model behavior exhibits when the snow heat capacity is considered that warrants further investigation. Highlights: A modified thermodynamic sea ice model is described. The number of ice layer is increased and the snow heat capacity is considered. Implementation of a vertically varying salinity profile in sea ice model. Implementation of a heat conductivity parameterization scheme in sea ice model. Ice thickness simulation is improved due to modifications in sea ice thermodynamic.